Early and sustained symptom improvement with umeclidinium/vilanterol versus monotherapy in COPD: a post hoc analysis of the EMAX randomised controlled trial. (May 2020) - Kerwin, Edward M; Boucot, Isabelle H; Vogelmeier, Claus F; Maltais, Francois; Naya, Ian P; Tombs, Lee; Jones, Paul W; Lipson, David A; Keeley, Tom; Bjermer, Leif
Background: In chronic obstructive pulmonary disease (COPD), both the time needed for patients to gain symptom improvement with long-acting bronchodilator therapy and whether an early response is predictive of a sustained response is unknown. This study aimed to investigate how quickly meaningful symptom responses are seen in patients with COPD with bronchodilator therapy and whether these responses are sustained. Methods: Early MAXimisation of bronchodilation for improving COPD stability (EMAX) was a 24-week, double-blind, double-dummy, parallel-group trial that randomised patients to umeclidinium/vilanterol (UMEC/VI), umeclidinium or salmeterol. Daily Evaluating Respiratory Symptoms in COPD (E-RS:COPD) score and rescue salbutamol use were captured via an electronic diary and analysed initially in 4-weekly periods. Post hoc analyses assessed change from baseline in daily E-RS:COPD score and rescue medication use weekly (Weeks 1–8), and association between E-RS:COPD responder status at Weeks 1–4 and later time points. Results: In the intent-to-treat population ( n  = 2425), reductions from baseline in E-RS:COPD scores and rescue medication use were apparent from Day 2 with all treatments. Treatment differences for UMEC/VI versus either monotherapy plateaued by Week 4–8 and were sustained at Weeks 21–24; improvements were consistently greater with UMEC/VI. For all treatments, most patients (60–85%) retained their Weeks 1–4 E-RS:COPD responder/non-responder status at Weeks 21−24. Among patients receiving UMEC/VI who were E-RS:COPD responders at Weeks 1–4, 70% were responders at Weeks 21–24. Conclusion: Patients with symptomatic COPD had greater potential for early symptom improvements with UMEC/VI versus either monotherapy. This benefit was generally maintained for 24 weeks. Early monitoring of treatment response can provide clinicians with an early indication of a patient's likely longer-term response to prescribed bronchodilator treatment and will facilitate appropriate early adjustments in care. Clinical Trial Registration: NCT03034915, 2016-002513-22 (EudraCT Number). The reviews of this paper are available via the supplemental material section.